Modulation of the Conductance-Voltage Relationship of the BK(Ca) Channel by Mutations at the Putative Flexible Interface between Two RCK Domains - Kim, Hyun-Ju (The Biophysical Society, 2008)
Calcium-dependent gating of the large-conductance Ca(2+)-activated K(+) (BK(Ca)) channel is conferred by the large cytosolic carboxyl terminus containing two domains of the regulator of K(+) conductance (RCK) and the high-affinity Ca(2+)-binding site (the Ca(2+)-bowl). In our previous study, we located the putative second RCK domain (RCK2) and demonstrated that it interacts directly with RCK1 via a hydrophobic “assembly interface”. In this study, we tested the structural model of the other interface, the “flexible interface”, by strategically positioning charge pairs across the putative interface. Several charge mutations on RCK2 affected the voltage-dependent activation of the channel. In particular, the Gly-to-Asp substitution at position 803 profoundly affected channel activation by stabilizing the open conformation of the channel with minimal effects on its Ca(2+) affinity and voltage sensitivity. Various mutations at Gly-803 shifted the channel's conductance-voltage curve either left or right over a 145-mV range. Since this residue is predicted to be in the first loop of RCK2 these results strongly suggest that this loop plays a critical role in determining the intrinsic equilibrium constant for channel opening, and they support the hypothesis that this loop is part of an interface that mediates conformational coupling between RCK1 and RCK2.